PENINGKATAN KUALITAS PEMBELAJARAN MENYIMAK CERPEN DENGAN MENGGUNAKAN MEDIA REKAMAN PEMBACAAN CERPEN PADA SISWA KELAS XI IPA2 SMA NEGERI 1 BONTOTIRO KABUPATEN BULUKUMBA - Andi Nurfaizah (Paedagogia: Jurnal Pendidikan, 2021)
Improving the Quality of Learning to Listen to Short Stories by Using Recorded Media for Reading Short Stories for Class XI IPA2 Students of SMA Negeri 1 Bontotiro, Bulukumba Regency.” This study aims to describe the improvement in the quality of learning to listen to short stories using short story reading recording media for students of class XI IPA2 SMA Negeri 1 Bontotiro, Bulukumba Regency. The results of the study prove that improving the quality of learning to listen to short stories using short story reading recording media in class XI IPA2 SMA Negeri 1 Bontotiro Bulukumba Regency at the planning stage found an increase in the ability of teachers in the field of study to plan better learning implementation in cycle II. In the implementation stage, there was an increase in student activity during the learning process, such as the sincerity, discipline, and self-confidence of students following the learning process. The evaluation stage found an increase in the results of the short story listening test, showing that in the first cycle 56.09% of students experienced mastery learning, and in the second cycle it reached 97.56% who experienced learning mastery. Based on the results of the study, it was concluded that the recording media for reading short stories could improve the quality of learning to listen to short stories in class XI IPA2 SMA Negeri 1 Bontotiro, Bulukumba Regency